Anatomical Variation in the Mandibular Foramen in Non-Atrophic and Atrophic Mandibles - Marcelo Betti Mascaro; Lara Cristina Picoli; Stefany Torres Reis Matos; Silvana Carla Sipos Lotaif; Mônica Rodrigues De Souza; Marcelo Ferreira Calderon (eJournal of Oral Maxillofacial Research)
Objectives: Previous studies of variation in mandibular foramen characteristics with age have involved comparison in different populations, but few data, between non-atrophic and atrophic mandibles are available. The aim of this original article was to compare the position, shape and area of the mandibular foramen between non-atrophic and atrophic mandibles.